Biomechanical performance of a novel zero-profile interbody cage: A cadaveric study - Jia Zhu; Yangyang Cui; Hangkai Shen; Zhenhua Liao; Hongsheng Gu; Weiqiang Liu (PLoS ONE, 2025)
Zero-profile cage (ZPC) products have been widely used in anterior cervical decompression and fusion (ACDF) surgery. To develop a ZPC that meets the biomechanical requirements of the Chinese population, we designed a novel zero-profile cage (NZ) by analyzing the critical anatomical parameters of the cervical spine in healthy Chinese people. This study aims to investigate and assess whether the biomechanical properties of the newly designed NZ could satisfy the criteria for clinical application. The biomechanical properties of the NZ were evaluated by being implanted into cervical cadaveric specimens, measuring and analyzing the range of motion (ROM) of surgical segments. The experimental group in this study consisted of the NZ. As the control group, the gold standard product combination of ACDF surgery, anterior fixation plate combined with cage (P + C), and the FDA-approved ZPC product (Zero-P) were utilized. The experiment utilized six cadaveric specimens of human cervical vertebrae subjected to identical testing conditions. Following the completion of the test under intact conditions, fusion products were implanted into each specimen in segment C4-C5 in the following order: Zero-P, NZ, P + C. Biomechanical results revealed that the ROM of the surgical segment had decreased significantly under six basic working conditions following NZ implantation. Statistically significant differences were observed in the left bending (LB), right bending (RB), and left rotation (LR) conditions when compared to the intact conditions. The remaining working conditions did not exhibit a significant difference. However, the observed decreasing trend was consistent with previously documented research. In terms of the ROM of surgical segments, there was no statistically significant difference between the NZ group, the Zero-P group, and the P + C group. The biomechanical properties of the newly designed NZ in this study were superior, comparable to the fusion effect observed in conventional products of the Zero-P group and the P + C group. Furthermore, the biomechanical properties exhibited further improvement when subjected to LB and RB conditions. In the future, the newly designed NZ has great potential as a competitive choice for clinical applications.